Laboratory and small plot fungicide trials to control potato late blight (Phytophthora infestans) next to Sepsiszentgyörgy town (Romania) - József, Attila; Bartók, Katalin (Acta Agraria Debreceniensis, 2014)
Our experiments were carried out during 2009 and 2010 years on Szépmező field, next to the Sepsiszentgyörgy town, Kovászna county, Romania. The experimental area situated at 520 - 580 m altitude, its soil is a humus rich chernozem, the yearly average temperature is between 7 - 8 oC, the precipitation is 500 - 600 mm/year. 7 different fungicides efficacy were studied for control to potato late blight disease caused by Phytophthora infestans on three potato varieties, viz. Ostara, Santé and Desirée. In the laboratory the fluanizam (500 g/L, ALTIMA 500) fungicide was the best in inhibition of growing fungus while on the field trial plots cymoxanil + famoxadone (22.1 + 16.6%, EQUATION PRO WP*) and metalaxyl** + mancozeb (200 g/L + 1.600 g/L, RIDOMIL MZ 72WP) were the most effective. This facts were confirmed by statistic Duncan-test and data of yields. The appearance of Phytophthora infestans epidemic was influenced by the climate conditions too during May and June when the minimum temperature was 12 oC, and the maximum 20 oC, the rain quantity more than 120 mm, the air humidity above 75%, these conditions promote the appearance and spread of fungus.